Perceived Self-efficacy and Information Literacy Skills as Influencing factors for Reference Service Delivery in Academic Libraries, South-West, Nigeria. - Awodoyin, Anuoluwa F.; Okiki, Olatokunbo Christopher (Communicate: Journal of Library and Information Science, 2022)
Reference service delivery will continue to evolve due to users’ changing information needs which are occasioned by the availability of information communication technology (ICT). This study investigated perceived self-efficacy and information literacy skills of reference librarians as correlates of reference service delivery in selected academic libraries in South West, Nigeria. The study is a survey based on the ex post facto type. The purposive sampling technique was used to select the universities sampled based on a research assumption that universities established for more than ten years should have a standard reference section. While the total enumeration technique was used to select all the sixteen reference librarians in the selected academic libraries. The questionnaire was the main data collection instrument. All questionnaires administered were returned and found useful for the study. The findings of the study revealed that the majority or 15 (93.8%) agreed that they have requisite self-efficacy for reference service delivery. The information literacy skills of the reference librarian showed that the most reliable information source they will recommend to users is a textbook (9(56.3%). Similarly, the study found there is a significant positive correlation between the reference librarian’s perceived self-efficacy, information literacy skills and reference service delivery. The study concluded that although the reference librarians showed a high self-efficacy in their ability to provide reference service, however in practice as information professionals this cannot culminate in being information literate. Hence, reference librarians need to improve their information literacy skills as image-makers of the library to meet up with changing user information demands.